A Conceptual History of Gifted Education - Gil Jr., Tyrone O. (Educative: Jurnal Ilmiah Pendidikan, 2026)
This paper traces the historical evolution of giftedness conceptualization from ancient philosophical foundations to modern psychometric paradigms, delineating shifts from demystification (scientific scrutiny of divine/mystical traits) to identification and emerging transactional models emphasizing context and equity. Employing a narrative literature review of primary texts and secondary analyses, it examines philosophical founders—Plato's meritocratic "golden souls", Aristotle's neurotic genius, Locke's nurtured "natural genius"  Rousseau's natural education, Kant's artistic originality, Schopenhauer's idea-contemplating anomaly and modern pioneers like Galton's hereditarianism, Terman's longitudinal studies, Binet's modifiable judgment, Lombroso's pathological degeneration, Yoder's early recognition, and Cattell's mental tests. Findings reveal embedded elitism and inequities, urging inclusive, ethical practices for dynamic potential realization.